The Role of Brand Anthropomorphism In Shaping Brand Love and Brand Loyalty To European Car Consumers In Indonesia - Widya, Pramatatya Resindra; Mursalin, Adi (Journal Research of Social Science, Economics, and Management, 2023)
This study will examine the influence of brand anthropomorphism and brand experience on brand love and its impact on brand loyalty with perceived price fairness as the moderation variable. The research uses a quantitative approach with a survey method. The sample in this study amounted to 250 European car users spread across DKI Jakarta, DI Yogyakarta, Central Java, East Java. The analysis model in this study will be divided into 3 stages of analysis. The first stage is multiple regression analysis, the second stage is simple regression analysis. The third stage of the moderation test with hierarchical moderated regression Brand anthropomorphism had a positive effect on the formation of brand love. Brand experience also has a positive and significant effect on brand love. Brand love has a positive effect on brand engagement. perceived price fairness does not moderate the relationship between brand love and brand engagement. For further research it is suggested to add subjective norm variables to this research model.